A description of the projects undertaken by the first Kansas City Design Center Urban Design Studio and recommendations on how to improve the student experience - Griffiths, Clark (Kansas State University, 2010)
The Kansas City Design Center (KCDC) Interdisciplinary Urban Design Studio is one of a myriad of design studios throughout the country, which seek to bring students of differing educational backgrounds together in an urban environment. In this setting they collaborate with each other, faculty, and outside professionals in an effort to stem many of the problems associated with urban America today. While these design studios have made their goals and objectives clear to the public and their studio participants, what are they offering in terms of a quality interdisciplinary educational experience? How interdisciplinary are these urban design studios? Are students receiving the same educational experiences? The above questions can only be answered by documenting the processes involved as well as looking to the students for their insight and feelings of their own individual educational experiences while taking part in the studio. The Kansas City Design center builds its educational endeavors around its interdisciplinary design studio. The goal of this studio is to “strengthen the educational experiences of future planning and design practitioners by engaging university faculty and students with real world issues facing Kansas City’s built environment.” Through this studio, faculty and students are able to work closely with local client groups working towards improving the built environment in Kansas City. If Kansas State University and the University of Kansas continue to send students to KCDC to study each year, it only seems appropriate that their faculty and potential students understand what is taking place at this particular studio. Therefore, the goal of this research paper is to describe the projects undertaken during the inaugural Kansas City Design Center Urban Design Studio and to analyze the interdisciplinary environment of the studio.
Keywords: Kansas City Design Center; Urban and Regional Planning (0999)